Developing A Parenting Guidance Program To Improve The Quality Of Parent-Child Relationships - Andika Apriansyah; Alfin Siregar; Siti Aisyah; Sofie Ahmira Rehgita Br Tarigan; Nidaul Ummah (Jurnal Multidisiplin Sahombu, 2024)
This study aims to identify the effectiveness of parenting guidance programs in improving the quality of the relationship between parents and young children. Using a qualitative approach with a case study method, the research explores parents' experiences during their participation in parenting guidance programs in early childhood education institutions (PAUD). Data were collected through semi-structured interviews with ten parent participants, participatory observations, and analysis of related documents. Data were analyzed using thematic analysis techniques to gain a comprehensive understanding of the program's intervention outcomes. The findings indicate that involvement in parenting guidance programs positively impacts parents' ability to understand the emotional and social needs of children, improves the quality of communication, and strengthens the emotional bond between parents and children. The program also facilitates the formation of social support networks among parents, reinforcing the implementation of positive parenting practices at home. Additionally, active involvement of facilitators as educators significantly contributes to the program's success. The study recommends that parenting guidance programs be widely adopted with the involvement of all stakeholders to achieve a harmonious parenting environment that supports optimal child development. The validity and reliability of the research data were enhanced through methodological triangulation involving interviews, observations, and documentation .